2017
DOI: 10.3892/etm.2017.4042
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale transcriptional analysis reveals key genes associated with the development of type II diabetes in mice

Abstract: Abstract. Diabetes mellitus is one of the primary diseases that pose a threat to human health. The focus of the present study is type II diabetes (T2D), which is caused by obesity and is the most prevalent type of diabetes. However, genome-scale transcriptional analysis of diabetic liver in the development process of T2D is yet to be further elucidated. Microassays were performed on liver tissue samples from three-, six-and nine-week-old db/db mice with diabetes and db/m mice to investigate differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Little is known about the impact of the non-catalytic PI3Kγ subunits in diabetes mellitus (DM). Recently, p87 was reported to be one of the key genes in murine liver tissue associated with the development of type II DM [188], whereas computational analysis suggest that the human p101 belong to a group of highly disordered proteins related to type II DM [189]; however, nothing is known about the relevance of these findings.…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%
“…Little is known about the impact of the non-catalytic PI3Kγ subunits in diabetes mellitus (DM). Recently, p87 was reported to be one of the key genes in murine liver tissue associated with the development of type II DM [188], whereas computational analysis suggest that the human p101 belong to a group of highly disordered proteins related to type II DM [189]; however, nothing is known about the relevance of these findings.…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%
“…A recent study by Fang et al (2018) showed that there is abnormal metabolism of lipids and fatty acids during gastrointestinal tumor metabolism. Phosphoinositide-3-kinase regulatory subunit 6 (PIK3R6) has been shown to be upregulated in the diabetes rat model, which was associated with the development of type II diabetes in mice ( Zhang et al, 2017 ). Moreover, PIK3R6 has been demonstrated to promote the proliferative and migratory potentials in ovarian cancer cells ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DHTKD1 , involved in lysine metabolism, was shown to reduce mitochondrial activity upon inhibition and might influence the development of diabetes 40 . Likewise, reduced GATM expression levels were indicated to affect the development of diabetes in a murine diabetes model 41 . This leads to the assumption that BPD individuals with psychotropic drug treatment seem to be more prone to develop diabetes compared to controls with resembling liver injury.…”
Section: Discussionmentioning
confidence: 99%